Climate change in the urban environment: Advancing, measuring and achieving resiliency. Issue 66 (December 2016) - Doherty, Meghan; Klima, Kelly; Hellmann, Jessica J.
Highlights: There has been increased attention directed towards climate change adaptation. Urban areas are increasingly seen as having a distinct role, and distinctive motivation and capacity, for adaptation. Two key themes emerge in this issue: 1) current barriers and 2) frameworks/metrics to identify and track adaptation progress. Careful measurement that enables investment by private and public parties is necessary to provide efficient outcomes that benefit the greatest number of people. Abstract: Climate change poses new and unique challenges that threaten lives and livelihoods. Given the increasing risks and looming uncertainty of climate change, increasing attention has been directed towards adaptation, or the strategies that enable humanity to persist and thrive through climate change the best it can. Though climate change is a global problem often discussed at the national scale, urban areas are increasingly seen as having a distinct role, and distinctive motivation and capacity, for adaptation. The 12 articles in this special issue explore ways of understanding and addressing climate change impacts on urban areas. Together they reveal young but rapidly growing scholarship on how to measure, and then overcome, challenges of climate change. Two key themes emerge in this issue: 1) that we must identify and then overcome current barriers to urban adaptation and 2) frameworks/metrics are necessary to identify and track adaptation progress in urban settings. Both of these themes point to the power of indicators and other quantitative information to inform priorities and illuminate the pathway forward for adaptation. As climate change is an entirely new challenge, careful measurement that enables investment by private and public parties is necessary to provide efficient outcomes that benefit the greatest number of people.